Study of weld bead geometry for GMAW additive manufacturing of duplex stainless steel - Wang Huifeng; Klarić Štefanija; Havrlišan Sara (FME Transactions, 2025)
The application of the Gas Metal Arc Welding (GMAW) Additive Manufacturing (AM) process for producing duplex stainless steel components can reduce material waste and enable control of the microstructure and alloy composition in different regions of the product through careful selection and adjustment of welding parameters. However, because achieving a higher deposition rate, greater reinforcement and penetration, and a narrower bead width must be balanced, simply setting welding parameters may not always yield the desired results. Therefore, the aim of this research is to analyze the effects of voltage, wire feed speed (WFS), and travel speed (TS) to determine their optimal values using experimental design methods. Grey Relational Analysis (GRA) was employed for multi-objective optimization, resulting in the following optimal parameters: voltage (16.783 V), WFS (403.231 cm/min), and TS (24.862 cm/min). These parameters were then applied to fabricate a 10-layer AM wall, achieving stable arc behavior, good interlayer bonding, and consistent wall morphology.